Comparative Analysis of Implant Survival in Diabetic vs. Non-Diabetic Patients: A Case-Control Study - Awais Hussain, Muhammad Hamza Hashim, Miral Shad, Mahvish Wahad Khan, Muhammad Amjad Bari, Rana Modassir Shamsher Khan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Dental implant therapy has become a reliable option for prosthetic rehabilitation; however,systemic conditions such as diabetes mellitus may compromise osseointegration and implantsurvival. This case-control